2014
DOI: 10.4103/2230-973x.138348
|View full text |Cite
|
Sign up to set email alerts
|

Albumin nanoparticles coated with polysorbate 80 as a novel drug carrier for the delivery of antiretroviral drug-Efavirenz

Abstract: Purpose of the study:The antiretroviral therapy (ART) has dramatically improved human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome (AIDS) treatment, prevention and also has been found to increase the lifespan of HIV/AIDS patients by providing durable control of the HIV replication in patients. Efavirenz is a non-nucleoside reverse transcriptase inhibitor of HIV-1. The purpose of this study is to formulate efavirenz-loaded bovine serum albumin nanoparticles to improve efavirenz delivery into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…DSC was performed by a diamond differential scanning calorimeter (model Diamond DSC, PerkinElmer Inc., Waltham, MA, USA). Samples were heated from 30 to 230°C at a scan speed of 5°C/min (Jenita et al 2014). The NPs' chemical structure was assessed by Fourier-transform infrared spectroscopy (FTIR, model IFS 66 s/v, Bruker, Ettlingen, Germany) using KBr discs.…”
Section: Preparation Of Cur@anps Dox@anps and Cur/ Dox@anpsmentioning
confidence: 99%
See 1 more Smart Citation
“…DSC was performed by a diamond differential scanning calorimeter (model Diamond DSC, PerkinElmer Inc., Waltham, MA, USA). Samples were heated from 30 to 230°C at a scan speed of 5°C/min (Jenita et al 2014). The NPs' chemical structure was assessed by Fourier-transform infrared spectroscopy (FTIR, model IFS 66 s/v, Bruker, Ettlingen, Germany) using KBr discs.…”
Section: Preparation Of Cur@anps Dox@anps and Cur/ Dox@anpsmentioning
confidence: 99%
“…These results validated the encapsulation of a single drug or both the drugs in the BSA matrix. Additionally, the DSC spectra of the NPs did not show the melting point peak(s) of Cur and/or Dox, which suggested that the drugs were in an amorphous state upon encapsulation in the NPs (Jenita et al 2014) (Fig. 1D).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] These research activities were stimulated by experiments which showed that nanoparticles penetrated e±ciently through the blood-brain barrier. 5 However, a commercial product for nanoparticle-assisted delivery of drugs through the cutaneous barrier is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A study was carried out to assess the stability of BSA nanoparticles of drug stavudine (drug-polymer ratio 1:1). The samples were stored in room temperature (15-20°C), refrigerator (3-5°C), and 37°C (Relative humidity [RH] = 75%) over a period of 3 months [16]. Samples were evaluated at 0, 1, 2, and 3 months for their drug content as well as any changes in their physical appearance.…”
Section: Stability Studiesmentioning
confidence: 99%